Structural parameters for the Galactic dwarf spheroidals - Irwin, M.; Hatzidimitriou, D. (1995)
A new determination of the structural parameters of the dwarf spheroidals (dSphs) orbiting our Galaxy is presented. The morphology of the dSphs was determined from star counts made using photographic plates digitized and analysed using the APM facility at Cambridge. Global and central mass-to-light ratios were calculated for these galaxies. They range from ~=10 for Fornax and Sculptor to more than 200 for Draco. It appears plausible that Draco, Ursa Minor, Carina and Sextans contain significant amounts of dark matter, at least under the standard assumptions for the dynamics of these galaxies. However, the errors associated with these estimates remain - often forbiddingly - large, dominated (in most cases) by the errors in the luminosity and velocity dispersion. The possibility of the presence of extra-tidal stars in at least some of the dSphs is also discussed, together with the effect of the Galactic tidal field on the dSphs' morphology. Both Sextans and Sculptor appear to be good candidates for systems in the process of tidal disruption.
Keywords: DARK MATTER; GALAXIES: STRUCTURE; Galaxy: structure